Standardized Application of Urine Pressure Measurement in Urinary Retention of Spinal Cord Injury - Xiangxia MENG; LI Li; Jun LENG; Ziyun FENG; Jinglong SUN (康复学报)
Objective:To explore the application of bladder volume and pressure in neurogenic bladder, which would provide quantitative basis for clinical neurogenic bladder management.Methods:Seventy-two patients with neurogenic bladder were randomly assigned into experimental group (n=36) and control group (n=36) based on random number table. The patients in the control group were taken the current nursing management of intermittent catheterization without bladder pressure test. The patients in the experimental group were taken bladder urinary pressure measurement before intermittent catheterization and conducted intermittent catheterization under the guidance of bladder urinary pressure value. Moreover, the residual urine and micturition times were recorded, and bacterial culture of urine was performed.Results:Both groups got improved 24 hour urination from the second week. The average number of urination, the average urine volume, the average number of leakage, residual urine volume, bladder safety capacity and urine culture bacteria significantly improved from the forth week onward compared with that before treatment (P<0.05). The difference of the average number of urination, the average urine volume, the average number of leakage, residual urine volume, bladder safety capacity and urine culture bacteria between two groups from the forth week onward were statistically significant (P<0.05).Conclusion:Urinary bladder pressure measurement can provide quantitative basis for the scientific management of neurogenic bladder in spinal cord injury (SCI), and can reduce urinary tract infection effectively, improve urination function and patient's life quality.